A descriptive qualitative study exploring youth with intellectual disabilities participation in the community of Moshi - Ephraim, Anthony (Division of Occupational Therapy, 2024)
Introduction: Youth with intellectual disability (YID) in Tanzania are at an impasse, as they face potential exclusion from accessing services and participation in their community. This is due to existing negative cultural beliefs, lack of awareness of the needs and abilities, and limited government services. For youth attending the Gabriella Children's Rehabilitation Centre (GCRC) occupational therapy services, little is known about how they engage in occupations in the community following occupational therapy intervention nor has research been conducted to date in this regard. Such insight would be important in recognizing factors that enable or hinder youth with intellectual disability participating within their communities after rehabilitation services. Research question: How do youth with intellectual disabilities engage in occupations in the community of Moshi Kilimanjaro and what enables their participation? Aim: The study aimed to describe how youth with intellectual disabilities participate in occupations in the Moshi community, Kilimanjaro Region, Tanzania. Method: A descriptive qualitative research approach with semi-structured interviews was used to collect data from eight participants and analyzed using a thematic analysis. The ethical principles of ensuring autonomy, non-maleficence, beneficence and justice guided the research. Findings: Two major themes were identified. The first theme; ''Becoming who I can be through what I can do” with two sub-themes, namely, “Opportunities at Gabriella Centre” and “Changes and development;” and the second theme; “Connecting and earning community trust through valued occupation and routines” with three sub-themes, being; “Valued occupational routines at home and in the community”; “Trusted, given responsibility and making choices”, and “Community acceptance and support”. Discussion: The occupational based intervention for YID offered by GCRC provided considerable practical skills that facilitated YID's participation in community life. The youth became confident, and their abilities were recognized, bringing about more community acceptance. YID contributed to alleviating poverty through their engagement in the valued family and community routines. The person-centered approach was used to guide youth to make informed occupational choices. Various facets of the environment were identified as enablers and barriers to community participation. Conclusion: A well-designed program that uses a person-centered approach and reflects valued community occupations, such as the GCRC, is necessary for YID to learn skills and use their ability to participate and contribute to the community. However, it is essential to consider holistically the needs of YID. Existing policies and laws coupled with supportive families and communities can contribute to successful community participation for YID. Abstract Word Count: 396 Keywords: Youth with intellectual disability; community participation; vocational skills; household chores; valued occupations